MODERN UNIVERSITY SOCIAL RESPONSIBILITY: CONCEPTUAL BASIS AND DEVELOPMENT DIRECTIONS IN THE CONTEXT OF HIGHER EDUCATION QUALITY ASSURANCE - Iliichuk, Liubomyra (Mountain School of Ukrainian Carpaty, 2022)
The article substantiates the essence of modern university social responsibility and reveals its influence on ensuring higher education quality. The connection between university social responsibility and higher education quality is determined when social responsibility is primary. The quality of higher education is its derived component. It has been proved that social responsibility characterizes a higher education institution's responsibility to society for the results and quality of educational activities, the transfer of socially recognized values to students, and their integration into society. It is noted that the social responsibility of a higher education institution is realized through the following components: a generator of educational services, an employer, a participant in social relations, a participant in economic and political relations with the state, and a business partner. The priority directions of the development of the university's social responsibility, which connects its educational activity, the system of relations, values, norms, and principles adopted in it with obligations to society and various categories of stakeholders, are revealed. The components, effective mechanisms, and relevant markers for evaluating the quality of higher education in the context of university social responsibility have been identified, including higher education students’ knowledge and competencies; meeting stakeholders’ needs and demands; processes, and areas of activity of the higher education institution; the results of the university functioning and the vital activities of the higher education system. The identified components constituting the evaluation mechanism – knowledge and competencies, stakeholders, processes, and results of the university’s activity – are interrelated, and only in a relationship can guarantee the quality of educational activities in a particular higher education institution.